Diets of mammalian carnivores in the deserts of north-eastern South Australia. (May 2021) - Vernes, Karl; Jackson, Stephen M.; Elliott, Todd F.; Tischler, Max; Harper, Andrew
Abstract: We studied diets of feral cats ( Felis catus ), dingoes ( Canis familiaris ) and red foxes ( Vulpes vulpes ) in desert environments in north-eastern South Australia by analysing prey remains in opportunistically-collected scats. Four major landscapes were sampled (Simpson Desert, Sturt Stony Desert, Strzelecki Desert – Cooper Creek and Diamantina River) which yielded 238 cat scats, 298 dingo scats and ten fox scats. There was some overlap in prey eaten by cats and dingoes, but their diets were significantly different because cats typically ate small prey such as small mammals, small lizards and birds, while dingoes ate larger prey like domestic cattle, kangaroos and large reptiles. The few fox scats collected suggested fox diets were more similar to cat than dingo diets. Scat composition also differed significantly between landscapes irrespective of predator, with landscapes differing both in diversity and relative abundances of prey consumed. We detected several species in scats that are threatened with extinction either nationally (dusky hopping mouse, Notomys fuscus, and crest-tailed mulgara, Dasycercus cristicauda ) or regionally (desert mouse, Pseudomys desertor, and long-haired rat, Rattus villosissimus ), adding valuable knowledge to the distribution of these mammals and demonstrating the value of predator scat analyses in mammal surveys of Australian deserts. Highlights: Diets of three predators were examined in contrasting Australian desert landscapes. Diets differed because cats ate mostly small prey while dingoes ate larger prey. Diets also differed significantly between the different landscapes. Several threatened species were detected, adding knowledge of their distribution. Our work demonstrates the value of predator scats for Australian desert surveys.